Manual muscle test at C5 palsy onset predicts the likelihood of and time to C5 palsy resolution. (February 2016) - Macki, Mohamed; Alam, Ridwan; Kerezoudis, Panagiotis; Gokaslan, Ziya; Bydon, Ali; Bydon, Mohamad
Highlights: We examined the prognostic factors and time to C5 palsy resolution after surgery. We studied 43 patients with C5 palsy over a 7-year period. Manual muscle test (MMT) score at the onset of C5 palsy correlates to chance of resolution and recovery time. Female gender is associated with a higher hazard of resolution. Abstract: The primary objective of this study was to identify time to and prognostic factors of C5 palsy resolution. All patients over a 7 year period who experienced C5 palsy following a posterior decompression and instrumented fusion surgery were retrospectively reviewed. C5 palsy resolution was defined as a recovery of deltoid muscle function equal to or greater than the preoperative condition as defined by the manual muscle test (MMT). Of the 511 patients who met the selection criteria, 8.6% (n = 44) experienced C5 palsy. MMT information was available for 43 patients; 81.4% (n = 35) had full resolution from their condition. Of the 35 patients who resolved, the median MMT score at onset was 3−. Following a discrete-time proportional hazards model, the hazards of C5 palsy resolution increased by 19% for every one-grade increase in MMT score at symptom onset (hazard ratio [HR] = 1.19, p  = 0.005). Moreover, males displayed a 71% lower hazard of resolution than females (HR = 0.29, p  = 0.003). Following an adjusted Kaplan–Meier analysis, the median time to C5 palsy resolution was between 6 months and 1 year. In a multiple linear regression, a lower MMT score at the onset of C5 palsy predicted a longer time to C5 palsy resolution (coefficient = −0.19, p  = 0.003). Time to C5 palsy onset was not statistically associated with hazards of palsy resolution ( p  = 0.381) or time to resolution ( p  = 0.121). A higher MMT score at the onset of C5 palsy statistically significantly predicted a higher chance of resolution and a shorter recovery time. Female sex was also associated with a higher hazard of resolution.